Obligatory Military Service and Disciplining Cultural Mechanisms: Approaches to the Mapuche-Huilliche Case in the XX Century (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The objective of this article is to explore the impact that obligatory military service, which was established in 1900, has had in the cultural changes of the indigenous mapuche-huilliche world. Through the life history perspective and documentary analysis we point out the pedagogical and disciplining cultural mechanisms rooted in the practices, discourses, and institutional rituals of the Chilean Army and the effects they have on the identity of mapuche-huilliches and mestizos.
Keywords: mapuche-huilliche; Obligatory Military Service; disciplining cultural mechanisms; identity changes; Chilean Army